Microglial activation elicits a negative affective state through prostaglandin-mediated modulation of striatal neurons - Klawonn, Anna M.; Fritz, Michael; Castany, Silvia; Pignatelli, Marco; Canal, Carla; Similä, Fredrik; Tejeda, Hugo A.; Levinsson, Julia; Jaarola, Maarit; Jakobsson, Johan; Hidalgo, Juan; Heilig, Markus; et al. (Immunity (Cambridge, Mass.), 2021)
Microglia are activated in many neurological diseases and have been suggested to play an important role in the development of affective disorders including major depression. To investigate how microglial signaling regulates mood, we used bidirectional chemogenetic manipulations of microglial activity in mice. Activation of microglia in the dorsal striatum induced local cytokine expression and a negative affective state characterized by anhedonia and aversion, whereas inactivation of microglia blocked aversion induced by systemic inflammation. Interleukin-6 signaling and cyclooxygenase-1 mediated prostaglandin synthesis in the microglia were critical for the inflammation-induced aversion. Correspondingly, microglial activation led to a prostaglandin-dependent reduction of the excitability of striatal neurons. These findings demonstrate a mechanism by which microglial activation causes negative affect through prostaglandin-dependent modulation of striatal neurons and indicate that interference with this mechanism could milden the depressive symptoms in somatic and psychiatric diseases involving microglial activation. [Display omitted] •Chemogenetic activation of striatal microglia induces an aversive affective state•Chemogenetic inhibition of microglia blocks inflammation-induced aversion•Microglial interleukin 6 signaling and prostaglandin synthesis regulate affective state•Prostaglandin E2 from activated microglia reduces the excitability of striatal neurons Many pathological conditions are accompanied by microglial activation and negative mood, but it is unclear if the microglia contribute causally to the aversive state. Klawonn et al. reveal that striatal microglial activation induces negative affect and that IL-6 and prostaglandin dependent signaling in microglia is critical for inflammation-induced aversion.